(untitled) (Biological Sciences - PJSIR, 2020)
. The genetic architecture of yield in eggplant was studied in a nine parent half diallel cross. The values of mean square for GCA (general combining ability) and SCA (specific combining ability) were highly significant which suggested the presence of both additive and non-additive genetic variance in the population. The higher magnitude of GCA, as compared with SCA, indicated predominance of additive genetic variance. In most of the cases, the cross between poor and poor parents showed positive SCA effect for yield per plant, which indicated the higher yield. The estimates of better parent heterosis ranged from 3 to 90 percent and the mid-parent heterosis ranged from 30 to 105 percent. Analysis for genetic components of variation suggested that additive components were more important in the inheritance of yield per plant. This character was observed being controlled by two to three pairs of genes or groups of genes. Narrow sense heritability was 21 percent indicating probability of selection in generations. The graphical analysis also indicated wide genetic diversity among the parents.